Channelizing Afghanistan to Pakistan informal trade into formal channels - Khan Miankhel, Adil (International Food Policy Research Institute, 2016)
This paper focuses on assessing the possibility of bringing informal trade from Afghanistan to Pakistan into the legal channels by reducing tariff and tax differentials between Pakistan and Afghanistan. A basic model and illustrative example are presented that encompass the monetary incentives of smugglers and shows possible tariff/tax reductions that bring profits from informal trade below the breakeven point. The effects of price discounting of informally traded products in the Pakistan market and possible under-invoicing by traders are also taken into consideration.